(untitled) (Palimpsesto, 2026)
This article analyzes the transition of the Magdalena Navarrete collection, from the Londres 38 Digital Archive, from a personal archive into an archive of resistance. This process is examined through two documentary acts: first, when her son was detained and Magdalena chose to safeguard the documents as an act of emotional resistance driven by the affective bond with her son and the need to affirm existence amidst disappearance; and second, the donation and archival processing carried out by Leslie Araneda at the house of memory’s digital archive. Based on the analysis of the collection’s documents, this study allows us to understand how an archive born of maternal filiation is transformed into a political tool for resistance and the preservation of historical memory.